2015
DOI: 10.1038/cddis.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Variola virus F1L is a Bcl-2-like protein that unlike its vaccinia virus counterpart inhibits apoptosis independent of Bim

Abstract: Subversion of host cell apoptosis is an important survival strategy for viruses to ensure their own proliferation and survival. Certain viruses express proteins homologous in sequence, structure and function to mammalian pro-survival B-cell lymphoma 2 (Bcl-2) proteins, which prevent rapid clearance of infected host cells. In vaccinia virus (VV), the virulence factor F1L was shown to be a potent inhibitor of apoptosis that functions primarily be engaging pro-apoptotic Bim. Variola virus (VAR), the causative age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 56 publications
6
59
0
Order By: Relevance
“…Interestingly, the A179L E76:ssBid R81 ionic interaction is also found in the variola virus F1L:Bid complex in the form of F1L E143:Bid R83 (20), unlike the Bcl-x L , Mcl-1, A1, and Bcl-w complexes with Bid, where this interaction is absent (37,45,47,48). In contrast, the two additional ionic interactions present in the A179L:Bax BH3 complex formed by D80:K64 and K79:E61 are also conserved in the Bcl-2:Bax BH3 complex as D140:R64 and R139:E61 (36), whereas in the poxviral DPV022:Bax BH3 complex (26) and Mcl-1:Bax complex they are absent (49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the A179L E76:ssBid R81 ionic interaction is also found in the variola virus F1L:Bid complex in the form of F1L E143:Bid R83 (20), unlike the Bcl-x L , Mcl-1, A1, and Bcl-w complexes with Bid, where this interaction is absent (37,45,47,48). In contrast, the two additional ionic interactions present in the A179L:Bax BH3 complex formed by D80:K64 and K79:E61 are also conserved in the Bcl-2:Bax BH3 complex as D140:R64 and R139:E61 (36), whereas in the poxviral DPV022:Bax BH3 complex (26) and Mcl-1:Bax complex they are absent (49).…”
Section: Discussionmentioning
confidence: 99%
“…2B) or the unrelated viral Bcl-2 protein variola virus F1L ( Fig. 2C) (20). Bax BH3 binds to A179L in an equivalent manner (Fig.…”
Section: A179l:bh3 Motif Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, viral proteins can prevent the recruitment of ASC molecules, thus inhibiting the innate immune response and promoting a better environment for viral replication [137]. Numerous reports have shown that VACV encodes viral homologs of cellular proteins; for example, it encodes anti-apoptotic proteins with homology to the BCL-2 family that regulate the innate immune response by interacting with NLRP1 [138]. In detail, the F1L protein of VACV plays a key role in inhibiting the function of NLRP1, and this function depends on a specific region of F1L (residues 1-47).…”
Section: Inhibition Of Inflammasome Assemblymentioning
confidence: 99%
“…Both EVM025 and variola virus F1L were shown to be apoptosis inhibitors with EVM025 inhibiting Bak directly, whereas Bax-mediated apoptosis was inhibited via the sequestration of Bim (70). In contrast, variola virus F1L was only able to inhibit Bak-mediated apoptosis and did not show any ability to engage Bim (71). Both EVM025 and variola virus F1L harbor long N-terminal extensions prior to their Bcl-2 fold; however, neither has been functionally characterized.…”
Section: Discussionmentioning
confidence: 99%